2006
DOI: 10.1051/0004-6361:20053909
|View full text |Cite
|
Sign up to set email alerts
|

A new look into the Helios dust experiment data: presence of interstellar dust inside the Earth's orbit

Abstract: An analysis of the Helios in situ dust data for interstellar dust (ISD) is presented in this work. Recent in situ dust measurements with impact ionization detectors on-board various spacecraft (Ulysses, Galileo, and Cassini) showed the deep penetration of an ISD stream into the Solar System. The Helios dust data provide a unique opportunity to monitor and study the ISD stream alteration at very close heliocentric distances. This work completes therefore the comprehensive picture of the ISD stream properties wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 24 publications
0
79
0
1
Order By: Relevance
“…In addition to the Ulysses measurements which revealed a lack of small 0.3 µm ISD grains within 3 AU heliocentric distance, measurements by Cassini and Galileo between 0.7 and 3 AU showed that the detected interstellar particles were bigger than 0.5 µm, with grain masses increasing closer to the Sun (Altobelli et al , 2005bAltobelli 2004). The flux of these bigger particles did not exhibit temporal variations due to the solar-wind magnetic field like the flux of smaller particles observed by Ulysses.…”
Section: Interstellar Dust Inside the Heliospherementioning
confidence: 85%
See 1 more Smart Citation
“…In addition to the Ulysses measurements which revealed a lack of small 0.3 µm ISD grains within 3 AU heliocentric distance, measurements by Cassini and Galileo between 0.7 and 3 AU showed that the detected interstellar particles were bigger than 0.5 µm, with grain masses increasing closer to the Sun (Altobelli et al , 2005bAltobelli 2004). The flux of these bigger particles did not exhibit temporal variations due to the solar-wind magnetic field like the flux of smaller particles observed by Ulysses.…”
Section: Interstellar Dust Inside the Heliospherementioning
confidence: 85%
“…The data show distancedependent alteration of the interstellar dust stream caused by gravitational focussing by the Sun, solar radiation pressure, and electromagnetic interaction with the time-varying interplanetary magnetic field (IMF; Altobelli et al , 2005aAltobelli et al , 2005bMann and Kimura 2000;Landgraf 2000;Czechowski and Mann 2003). Radiation pressure and electromagnetic forces strongly depend on grain size, leading to a strong modification of the size distribution and fluxes of grains measured inside the heliosphere .…”
Section: Interstellar Dust Inside the Heliospherementioning
confidence: 99%
“…In 1993, the first ISD particles were identified in the Ulysses dust data (Grün et al 1993). Later, data from Galileo, Helios, and the early mission phase of Cassini were also analyzed with respect to ISD (Altobelli et al , 2005(Altobelli et al , 2006). An overview of related papers is given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Altobelli et al (2006); (2) Grün et al (1994); (3) Baguhl et al (1996); (4) Landgraf et al (2000); (5) Krüger et al (2007); (6) Baguhl et al (1996), (7) Altobelli et al (2005); (8) Altobelli et al (2003); (9) Krüger et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…From Mercury to Saturn, interstellar grains have been identified traversing the solar system. [1,39,40].…”
Section: Interstellar Dustmentioning
confidence: 99%